Pediatric Intensive Care Unit (PICU) Patient Room Design: Identifying Safety Risks in Mirrored Rooms Through a Graphical Systems Analysis. (January 2022) - Joseph, Anjali; Joshi, Rutali; Mihandoust, Sahar; Goel, Swati; Hebbar, Kiran; Colman, Nora
Objective: The objectives of this study are to graphically depict specific clinical challenges encountered in a mirrored pediatric intensive care unit patient room and to represent potential solutions to address these challenges using a systems approach. Background: The intensive care unit (ICU) patient room is a highly complex patient care environment where the design of the room must support patient care delivery safely and efficiently. There is a lack of research examining how ICU design elements interact with other system components to impact patient care. Methods: An observational case study method utilizing a systems approach was used to observe and graphically depict clinical challenges with mirrored room configurations and to identify potential solutions. Video recordings of the three clinical scenarios were analyzed in detail in conjunction with three rounds of interviews with a clinical expert. Results: Equipment or task characteristics that require orienting to a specific side of a patient create challenges in a mirrored room. In order to deliver care safely and efficiently in the mirrored room, adaptations would be required including changing boom, equipment and team member locations, purchasing new equipment, staff training, and inventory management. Some procedures such as extracorporeal membrane oxygenation would be difficult to conduct safely in the mirrored room, even with significant adaptations. Conclusion: Solutions to the challenges presented in mirrored room configurations are multifaceted and require simultaneous and ongoing changes to multiple systems elements, while others can be addressed relatively easily, for example, purchasing new equipment.